Mobile tour guide application with attraction recognition for UTAR Kampar campus - Lee, Mun Hong (2021)
UTAR Kampar Campus has a lot of unique and beautiful buildings and structures but many people seldom get the chance to know the histories and stories behind these buildings and structures. This is such a waste because most of the buildings in UTAR Kampar Campus is built with meanings and the designs are based on some unique ideas such as the Ling Liong Sik Hall, which resembles the Forbidden City Palace in China. This is because most of the people, even if they are interested, do not want to go through the hassle of searching for the web and digging for the information about the place. So, this project aims to resolve the issue. This project is to create an app that allows user to either take photo from their phone or select photo from gallery of a UTAR building or structure and the app will identify the building in the photo taken. Then, a brief history and description of the place will be shown. The app can accurately identify the buildings using a model trained by a machine learning algorithm, and GPS information to increase the accuracy. With this app, users can get to know the histories and stories of buildings and structures in UTAR Kampar Campus with ease without even having to search the Internet for information.